The last word - Anton Verwey; Jan Bredenkamp (Communicare)
A few weeks ago we were the fortunate recipients of Clicking by Faith Popcorn, proclaimed by Fortune Magazine to be “the Nostradamus of Marketing”. The subtitle of the book is “16 Trends to future fit your life, your work, and your business”. Nostradamus, here and now telling us about our future? As part of our strategy consulting work, we also read through a variety of magazines, journals and e-zines covering a wide range of disciplines, such as business, economics, politics and technology. Perhaps being more attuned to the trends we picked up because of Clicking, it dawned on us that almost all of the articles illustrated in some form or another a real shift in social patterns. This awareness raised a concern that perhaps what Clicking was doing was simply illustrating the surface of a much more substantial “social revolution”. Could it be that these trends are nothing more than the symptoms of a much more profound change?